2015
DOI: 10.3109/09593985.2015.1025321
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs towards mental illness in Turkish physiotherapy students

Abstract: Mental health is a new area of specialization for physiotherapists. However, they usually meet patients with psychiatric co-morbidities secondary to other chronic diseases. It is important to explore the beliefs of future physiotherapists regarding mental illness in order to implement effective strategies to avoid possible stigmatizing attitudes that may interfere with the rehabilitation process. Moreover, the psychiatric field should be introduced to physiotherapists as a clinical and research area. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
1
15
0
5
Order By: Relevance
“…Instead, part of stigma is its effect on a person's body and mind (e.g., higher levels of depression and cortisol levels in those who are stigmatized, feelings of disgust in those who stigmatize). 3,13,14 This thinking also reveals that stigma is evident in objects in the environment (e.g., equipment that fits only some bodies, images of thin people used in advertising), 7 in what a person can do, and in how a person can live (e.g., reduced employment opportunities, social standing, dating opportunities). 15 In health care specifically, stigma is apparent in decision making, interpersonal interactions, care judgments, personal perceptions, quality of professional practice, avoidance of health care by those who feel stigmatized, and a lack of trust in health care providers.…”
Section: How Can Physiotherapists Develop a Greater Understanding Of mentioning
confidence: 98%
See 1 more Smart Citation
“…Instead, part of stigma is its effect on a person's body and mind (e.g., higher levels of depression and cortisol levels in those who are stigmatized, feelings of disgust in those who stigmatize). 3,13,14 This thinking also reveals that stigma is evident in objects in the environment (e.g., equipment that fits only some bodies, images of thin people used in advertising), 7 in what a person can do, and in how a person can live (e.g., reduced employment opportunities, social standing, dating opportunities). 15 In health care specifically, stigma is apparent in decision making, interpersonal interactions, care judgments, personal perceptions, quality of professional practice, avoidance of health care by those who feel stigmatized, and a lack of trust in health care providers.…”
Section: How Can Physiotherapists Develop a Greater Understanding Of mentioning
confidence: 98%
“…For example, several studies and theoretical investigations (including some of my own) have claimed that physiotherapists inadvertently stigmatize particular characteristics, such as aspects of disability, mental illness, persistent pain, and obesity. [1][2][3][4][5][6][7][8] The authors of some of these investigations have also argued that physiotherapists (again inadvertently) lack an understanding of the stigma people might experience, thereby sometimes creating negative consequences for those they treat. 1,5,6 As a physiotherapist in one of my studies 6 said, ''I haven't thought about how [larger patients] would feel coming to see me.…”
mentioning
confidence: 99%
“…: niveaux de dépression et de cortisol supérieurs chez les victimes de stigmatisation, sentiments de dégoût chez ceux qui stigmatisent). 3,13,14 Cette approche nous permet aussi de détecter des manifestations de stigmatisation dans les objets de notre environnement (ex. : équipement qui ne convient qu'à certains types de corps, les images de minceur utilisées en publicité) 7 ainsi que dans les possibilités et le type de vie qui s'offrent à une personne (ex.…”
Section: Comment Les Physiothé Rapeutes Peuvent-ils Mieux Comprendre unclassified
“…Par exemple, selon un certain nombre d'études et d'enquêtes théoriques (dont certaines de mon cru), les physiothérapeutes stigmatisent involontairement des caractéristiques particulières, comme certains aspects des handicaps, des maladies mentales, des douleurs persistantes et de l'obésité. [1][2][3][4][5][6][7][8] De plus, selon les auteurs de certaines de ces enquêtes, les physiothérapeutes (toujours involontairement) comprennent mal la stigmatisation que peuvent vivre certaines personnes, ce qui entraîne des conséquences négatives pour les patients qu'ils traitent. 1,5,6 Comme l'a dit un physiothérapeute dans une de mes études 6 : « Je n'avais jamais réfléchi à la manière dont les patients en surpoids se sentent lorsqu'ils viennent me voir.…”
unclassified
“…What literature exists is limited to studies on the stigma of disability (Cassidy, Reynolds, Naylor, & De Souza, 2011;French, 1994;Gething, 1993;R. Johnson, 1993), mental illness (Probst & Peuskens, 2010;Yildirim, Demirbuken, Balci, & Yurdalan, 2015) and pain (Bunzli, Watkins, Smith, Schütze, & O'Sullivan, 2013;Slade, Molloy, & Keating, 2009;Synnott et al, 2015). Many of these studies highlighted that physiotherapists demonstrated stigma towards people with the attributes outlined above (French, 1994;Gething, 1993;Probst & Peuskens, 2010;Slade et al, 2009;Synnott et al, 2015;Yildirim et al, 2015), often at similar levels to the general population (French, 1994;Gething, 1993;Probst & Peuskens, 2010;Yildirim et al, 2015).…”
Section: Weight Stigma In Physiotherapymentioning
confidence: 99%